Oral pyogenic granuloma (excluding pregnancy tumour): a clinical analysis of 304 cases - Zain, R.B.; Khoo, S.P.; Yeo, J.F. (1995)
A clinical analysis of 304 cases of pyogenic granuloma (excluding pregnancy tumour) were obtained from the clinical evaluations submitted by clinicians while sending specimens for biopsy. The average age of the patients with pyogenic granuloma was 28.9 years with a peak age incidence in the second decade. More female patients were affected and the lesions present mainly in the Chinese. The majority of the lesions were ulcerated and pedunculated. The lesions had a mean diameter of 10.8 mm with a mean lesion duration of 6.0 months. The gingiva was the prevalent site for these lesions with a greater number being located in the maxilla. The recurrence rate was found to be 14.1.